An Injection from the Tip of your Pen: The Formation of Modern Romani Writing on the Pages of Románo ľil Magazine and its Predecessor Informační zpravodaj 1969--1973 - Ryvolová, Karolína (Romano džaniben, 2019)
This paper fills out some of the blanks in our knowledge about the earliest specimensof Romani press in the Czech Republic, Informační zpravodaj and Románoľil. It traces the history of struggle of Romani elites to establish their own ethnicmagazine from 1957 to 1990. As the said magazines also became the very firstplatform of consistent Romani literary works' publication, this study offersa comprehensive description of their so-far little known literary content along withthe basic analysis thereof, revealing some interesting new personalities which haveas yet escaped the attention of relevant scholars.
Keywords: Informační zpravodaj; Romani writing in the Czech Republic; Románo ľil; Union of Gypsies-Roma